Plantain flours as potential raw materials for the development of gluten-free functional foods - Gutiérrez Carmona, Tomy José (2018)
Plantain flour (Musa ssp., group AAB, sub-group clone Harton) was modified by acetylation, carboxymethylation, methylation, oxidation and phosphation, in order to determine which of these modifications produce a material with potential for the development of gluten-free products with improved nutritional properties. The structural, rheological and nutritional properties of the modified flours were investigated. The phosphated plantain flour, cross-linked with sodium trimetaphosphate (STMP), had a lower in vitro digestibility rate associated with resistant starch (RS) types RS2, RS4 and RS5. This latter was confirmed by the formation of the amylose-lipid complex as determined by XRD. All the flours tested had a C-type structure with the exception of the methylated plantain flour which produced a large quantity of reaction by-product (BaSO4). The phosphated plantain flour represents a raw material with great potential for the development of gluten-free food (bread and cookie) with functional properties, i.e. health benefits.